Public Policies for Territorial Cohesion - Medeiros, E. (2023)
This book introduces a comprehensive and updated analysis of the role of public policies to promote territorial cohesion processes and trends in a given territory. By being the first book taking a reflective and holistic approach on how public policies can lead to more cohesive and balanced territories, it advances theoretical avenues for academics and showcases current academic research to policymakers and practitioners by focusing on how public policies, being implemented in different territorial scales (urban, local, regional, national, and European), can actively contribute to foster territorial cohesion trends in a given territory. This reflective approach provides an opportunity for thinking about what lessons can be learned from past and ongoing experiences and how they can improve future implementation of public policies more effectively and efficiently toward territorial cohesion, since all existing analyses show that at the national level, no European country has achieved territorial cohesion trends over the past decades. As such, this book acts as a valid and useful policy manual that effectively contributes to inverting current territorial exclusion trends at the national level, by highlighting best policy practices and a comprehensive introduction to contemporary thinking about how public policies can play a decisive role in boosting territorial cohesion processes in a given territory.